G532(P) 'SCFN' (subcutaneous fat necrosis) of the newborn – an important differential diagnosis in evaluation for causes of bruise-like skin lesions in a neonate. (25th October 2020) - Khan, UA; Clifford, E; Moclair, M; Barry, R
Abstract : Introduction: SCFN of the newborn is an uncommon, self-limiting panniculitis characterized by development of erythematous, firm, indurated plaques or nodules commonly over the extremities, back, buttocks and thighs, mostly occurring in term or post term babies within the first few weeks after birth. Hypercalcaemia is a life threatening complication which requires monitoring for several months.Perinatal mechanical stress, tissue hypoxia, and hypothermia may contribute to the pathogenesis. Exact incidence is unknown with a nearly equal male to female ratio. Case Background: We report a neonate presenting to emergency department by parents at 10 days of life from home with a sudden onset bruise-like linear lesion 6 cm long and 1.5 cm wide extending from the midline of upper part of the back to the right axilla. There was no history of trauma and baby was born via NVD. The skin lesion was red/purple in colour, non tender and palpable on examination. Clinical examination was otherwise unremarkable. As the marks on the back were suggestive of bruising, the baby underwent detailed Non Accidental Injury (NAI) investigations and social services assessment. Coagulation studies and FBC were normal. MRI brain reported subdural haematoma and suspected skull fracture, making NAI a strong consideration. Ophthalmology assessment and skeletal survey were normal. CT Skull was advised and this excluded skull fracture in favour of vermian skull bones. The origin of the subdural haematoma was then deemed uncertain but reported to be likely associated with vaginal delivery. Dermatology consultation confirmed the clinical diagnosis of SCFN of newborn. Conclusion: SCFN is a rare but important condition to consider in young infants who present with unexplained bruise-like lesions which require thorough investigation and consideration of possible NAI. Dermatology opinion was very helpful and should be sought if there is uncertainty about differential diagnosis.